Are auditory-evoked frequency and duration mismatch negativity (MMN) deficits endophenotypic for schizophrenia? High-density electrical mapping in clinically unaffected first-degree relatives, recent-onset and chronic schizophrenia - GARAVAN, HUGH PATRICK (Elsevier, 2008)
Mismatch negativity (MMN) is a negative-going event-related potential (ERP) component that occurs in response to intermittent changes in constant auditory backgrounds. A consistent finding across a large number of studies has been impaired MMN generation in schizophrenia, which has been interpreted as evidence for fundamental deficits in automatic auditory sensory processing. The aim of this study was to investigate the extent to which dysfunction in MMN generation might represent an endophenotypic marker for schizophrenia.
PUBLISHED
Keywords: Psychiatry; schizophrenia